MACHINE TOOL AND MACHINING METHOD - TAKAHASHI HIKARU (2014)
A machine tool includes a main spindle (10) which holds a workpiece (200, object to be machined) and is rotatable about the shaft center (C1), a main spindle motor (20, main spindle driver) which rotates the main spindle (10), a rotary guide bush (30, eccentric guide hush) which supports the workpiece (200) projecting from a leading end of the main spindle (10) to be rotatable in a state of being eccentric relative to the shaft center (C1) by a length E, a guide bush servomotor (40, guide bush driver) which rotates the rotary guide bush (30) about the shaft center (C1) in synchronization with the main spindle (10), and a controller (50) which controls the rotation and driving of the guide bush servomotor (40), so as to selectively switch between the rotation state and the stop state of the rotation.